Targeting HRAS in Head and Neck Cancer: Lessons From the Past and Future Promise. Issue 5 (September 2022) - Desilets, Antoine; Ho, Alan L.
Abstract: HRAS mutations define a unique biologic subset of head and neck squamous cell carcinoma. Oncogenic HRAS is uniquely dependent on posttranslational farnesylation for membrane localization and activation of downstream signaling. Tipifarnib, a farnesyltransferase inhibitor, demonstrated encouraging antitumor activity for HRAS mutant head and neck squamous cell carcinoma and modest activity for HRAS mutant salivary gland cancer. New combination strategies to circumvent intrinsic and acquired resistance to TFIs are being investigated.